Pengaruh Motivasi Terhadap Prestasi Kerja Pegawai pada Kantor Kecamatan Lahewa - Aferiaman Telaumbanua (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Human resources are the most important thing in every organization or agency. The resources possessed by each employee in the form of energy, talent, and creativity as well as efforts for the progress of the organization are different, this is influenced by several aspects such as aspects of education, economic aspects and aspects of motivation. This research was conducted at the Lahewa District Head Office, North Nias Regency. In conducting research the authors use quantitative methods. The sample in this study were all employees at the Lahewa District Office in North Nias Regency totaling 22 people. Based on the hypothesis testing criteria it turns out that Ha is accepted and Ho is rejected where Ha is a relationship and Ho is not a relationship, because t arithmetic = 2,335> t table = 2,052 so that it can be stated that there is a significant relationship of Motivation (X) to Work Performance (Y) in Lahewa District.